Is commodity index investing profitable? - Tobias Fethke; Marcel Prokopczuk (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2018)
Using a comprehensive dataset of first, second and third generation commodity indices, we investigate the potential diversification benefits in equity-bond portfolios. The results show that first generation commodity indices are outperformed by enhanced indices. Second generation indices provide slightly increased portfolio Sharpe ratios but at the same time they are spanned by benchmark assets. For third generation commodity indices, the mean-variance spanning hypothesis is rejected but they show heterogenous out-of-sample performances. We thus present new evidence showing that the performance of the third generation of commodity indices is less clear-cut than found in existing studies.
Keywords: G11; 330; Commodities; Investing; Index